Saat Sebuah Desa Dibakar Menjadi Abu: Hak Ulayat Laut dan Konflik Antar Kelompok di Pulau Kei Besar - Dedi Adhuri (Antropologi Indonesia, 1998)
Marine tenure in Maluku has become the main focus in the discussion of traditional marine resource management in Indonesia. Unfortunately, this discussion remains unbalanced in the use of an approach which excessively emphasizes questions on the modes of sea resource management. The agents of management, together with the socio-cultural aspects of such people on relation to resource use, are barely raised. Based on these concerns, this paper will highlight the social context of marine tenure practices in Kei Islands, Southeast Maluku. Focusing on a conflict over coastal boundaries between two villages on Kei Besar Island, the paper demonstrates how people use the issue of marine tenure in the discourse and practice of precedence. The conflict reveals the power struggles of two social groups, the mel (noble) and the ren ('free people'), involved in the issue of sea territory and how each group interpreted and responded to changes occurring in their environment